Price and Wage Flexibility in Hong Kong SAR - Guo, Si (IMF Working Papers; Working Paper, 2017)
The paper assesses the price and wage flexibility in Hong Kong SAR. At the aggregate level, it compares Hong Kong SAR with the United States, the United Kingdom and Singapore by examining the three commonly used macroeconomic relationships among inflation, unemployment, wage growth, and output fluctuations. At the industry level, the paper compares the distributions of labor earnings and price growth in Hong Kong SAR and the United States. It further estimates a model of wage formation under downward nominal wage rigidity to compare the extent of wage rigidity in Hong Kong SAR and the United States. Overall, the comparisons show that broadly speaking, price and wage adjustments are more flexible in Hong Kong SAR than other economies.